A robot-assisted bilateral upper limb training strategy with subject-specific workspace: A pilot study - Miao, Qing; Zhang, Mingming; McDaid, Andrew; Peng, Yuxin; Xie, Sheng Q. (Robotics and autonomous systems, 2020)
This paper proposes a new robot-assisted bilateral upper limb training strategy, focusing on the bilateral coordination of users’ upper limbs. The strategy is implemented and evaluated on a bilateral upper limb rehabilitation device (BULReD) that is an H-bot mechanism actuated by two Maxon DC motors. The control system consists of a position controller, an admittance controller and an adaptive algorithm, where the BULReD stiffness is modified session by session based on training performance. This strategy is also integrated with subject-specific workspace for enhanced training safety. Experiments were carried out with five subjects through active reaching tasks. Results indicate that the proposed training strategy requires significant coordination of bilateral upper limbs for task completion, and is able to tune control parameters to an appropriate difficulty level based on participants’ training performance. Future work will focus on its clinical evaluation on patients with upper limb disabilities. •A robot-assisted bilateral upper limb coordination training strategy.•The strategy enables subject-specific workspace determination.•Experimental results support its potential for upper limb coordination training.